PENGUKURAN FEAR OF MISSING OUT PADA GURU: VALIDASI FoMOS - Novi Hidayat; Neulis Dewi Julaeha Daswilah; Iksal Maulana (Eudaimonia Journal Psychology, 2025)
The integration of digital technology in the teaching profession exposes educators to an intense flow of information, increasing their vulnerability to Fear of Missing Out (FoMO). Although FoMO has been extensively studied globally, research focusing on teachers particularly in Indonesia, where digital engagement is high remains very limited. This study aims to adapt and validate the Fear of Missing Out Scale (FoMOS) for the context of Indonesian teachers by examining its psychometric properties. A quantitative approach was employed, including content validation by experts (VI = 1), readability testing (VI = 1), and data collection from 68 vocational high school teachers using purposive sampling. Structural validity was analyzed using Confirmatory Factor Analysis (CFA). Results indicated a high KMO value (0.845), a three-factor structure with factor loadings ranging from 0.585 to 0.818, and strong reliability (0.973). Overall, this adapted FoMOS is both valid and reliable for measuring FoMO among Indonesian teachers.